Cooperative Learning Strategies in Citizenship Education Subject in Elementary Schools During the Pandemic Covid-19 - Finanti, Elinna Dyah; Marzuki, Marzuki (Jurnal Ilmu Pendidikan, 2021)
During the Covid-19 pandemic, teachers were worried about students’ character education because they could not directly monitor students’ character development. Digital learning-based learning has advantages and disadvantages, so teachers must provide the best learning strategies to achieve learning goals, especially in character education. The purpose of this research is to provide the best solutions in learning strategies during the Covid-19 pandemic. This research uses a qualitative approach with a descriptive research type. Data used in this study are primary data sources, namely teachers and related students, and secondary data sources, namely the documents required in this study. The data that has been obtained through the data collection process is grouped, then reduced, presented, and concluded. This research shows that students prefer and are more active when learning cooperative rather than having to use digital learning (online). Strengthening responsibility character education for students when using online knowledge has not been achieved. Therefore, the best solution to overcome these problems is to use direct cooperative learning to be more responsible with their lessons.